2001
DOI: 10.1093/humrep/16.6.1115
|View full text |Cite
|
Sign up to set email alerts
|

Uterine contractility decreases at the time of blastocyst transfers

Abstract: High-frequency uterine contractions at the time of non-cavitating embryo transfer influence adversely IVF-embryo transfer outcome. This prompted us to quantify prospectively the possible decline in uterine contraction frequency occurring during later stages of the luteal phase of ovarian stimulation, up to the time of blastocyst transfers, in 43 IVF-embryo transfer candidates. Contractility was assessed on the day of human chorionic gonadotrophin (HCG) administration, 4 days after HCG (non-cavitating embryo tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(129 citation statements)
references
References 15 publications
4
121
0
4
Order By: Relevance
“…4 Previous studies have shown that decreased uterine contractility during the later luteal phase and the larger sizes of blastocysts would prevent the retrograde passage of embryos, which imply that blastocyst ET reduces the rate of ectopic pregnancy compared with cleavage-stage ET. 5,6 These results support Chang and Suh's observation that transfer of three or more embryos with higher estimated embryo implantation potential was reported to be associated with an increased risk of ectopic pregnancy. 2 Moreover, two studies suggested that the rate of ectopic pregnancy was not reduced after blastocyst ET compared with cleavagestage ET.…”
Section: Introductionsupporting
confidence: 86%
“…4 Previous studies have shown that decreased uterine contractility during the later luteal phase and the larger sizes of blastocysts would prevent the retrograde passage of embryos, which imply that blastocyst ET reduces the rate of ectopic pregnancy compared with cleavage-stage ET. 5,6 These results support Chang and Suh's observation that transfer of three or more embryos with higher estimated embryo implantation potential was reported to be associated with an increased risk of ectopic pregnancy. 2 Moreover, two studies suggested that the rate of ectopic pregnancy was not reduced after blastocyst ET compared with cleavagestage ET.…”
Section: Introductionsupporting
confidence: 86%
“…It has been assumed that the risk of ectopic pregnancy could be decreased following day 5 transfer compared to day 3 embryo transfer because of the reduced uterine contractility and the larger diameter of the blastocyst [8,37]. In the present study, the ectopic pregnancy rates were identical (2.1 % in the blastocyst group and 2.0 % in the cleavagestage embryo transfer group).…”
Section: Discussionsupporting
confidence: 49%
“…Potential benefits of blastocyst transfer are a better selection of viable embryos and synchronization of embryonic stage with the endometrium in the presence of reduced uterine contractions [7,8]. Nevertheless, blastocyst transfer may have some drawbacks such as cancellation of embryo transfer because of not having a blastocyst to transfer after 5-day culture, a lower embryo cryopreservation rate and increased laboratory work.…”
Section: Introductionmentioning
confidence: 99%
“…Biervliet et al believe that uterine contractions are less harmful for day-5 ETs compared to day-2 to day-3 ETs due to the uterus-relaxing effects of progesterone [7]. Fanchin et al have shown earlier that uterus contractions significantly decrease 7 days after HCG application [8,9]. It is noteworthy that differences in the CPR and LBDR between ET 1-4 were less pronounced in patients receiving a day-3 ET compared to those with a day-5 ET (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These contractions seem to particularly occur after difficult ETs and might interfere with embryo implantation [5,6]. The impact of such contractions might even be more profound on day-3 as compared to day-5 ETs due to the influence of progesterone [7][8][9].…”
Section: Introductionmentioning
confidence: 99%